12(S)-HETrE, a 12-Lipoxygenase Oxylipin of Dihomo-γ-Linolenic Acid, Inhibits Thrombosis via Gαs Signaling in Platelets. Issue 10 (October 2016) - Yeung, Jennifer; Tourdot, Benjamin E.; Adili, Reheman; Green, Abigail R.; Freedman, Cody J.; Fernandez-Perez, Pilar; Yu, Johnny; Holman, Theodore R.; Holinstat, Michael
Abstract : Objective—: Dietary supplementation with polyunsaturated fatty acids has been widely used for primary and secondary prevention of cardiovascular disease in individuals at risk; however, the cardioprotective benefits of polyunsaturated fatty acids remain controversial because of lack of mechanistic and in vivo evidence. We present direct evidence that an omega-6 polyunsaturated fatty acid, dihomo-γ-linolenic acid (DGLA), exhibits in vivo cardioprotection through 12-lipoxygenase (12-LOX) oxidation of DGLA to its reduced oxidized lipid form, 12(S)-hydroxy-8Z, 10E, 14Z-eicosatrienoic acid (12(S)-HETrE), inhibiting platelet activation and thrombosis. Approach and Results—: DGLA inhibited ex vivo platelet aggregation and Rap1 activation in wild-type mice, but not in mice lacking 12-LOX expression (12-LOX −/− ). Similarly, wild-type mice treated with DGLA were able to reduce thrombus growth (platelet and fibrin accumulation) after laser-induced injury of the arteriole of the cremaster muscle, but not 12-LOX −/− mice, supporting a 12-LOX requirement for mediating the inhibitory effects of DGLA on platelet-mediated thrombus formation. Platelet activation and thrombus formation were also suppressed when directly treated with 12(S)-HETrE. Importantly, 2 hemostatic models, tail bleeding and arteriole rupture of the cremaster muscle, showed no alteration in hemostasis after 12(S)-HETrE treatment. Finally, the mechanism for 12(S)-HETrE protection was shown to be mediated via a Gαs -linked G-protein–coupled receptor pathway in human platelets. Conclusions—: This study provides the direct evidence that an omega-6 polyunsaturated fatty acid, DGLA, inhibits injury-induced thrombosis through its 12-LOX oxylipin, 12(S)-HETrE, which strongly supports the potential cardioprotective benefits of DGLA supplementation through its regulation of platelet function. Furthermore, this is the first evidence of a 12-LOX oxylipin regulating platelet function in a Gs α subunit–linked G-protein–coupled receptor–dependent manner. Abstract : Supplemental Digital Content is available in the text.